2011
DOI: 10.1103/physrevlett.106.204503
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Invariance in Three-Dimensional Rotating Turbulence

Abstract: We examine three-dimensional turbulent flows in the presence of solid-body rotation and helical forcing in the framework of stochastic Schramm-Löwner evolution curves (SLE). The data stems from a run on a grid of 1536 3 points, with Reynolds and Rossby numbers of respectively 5100 and 0.06. We average the parallel component of the vorticity in the direction parallel to that of rotation, and examine the resulting ωz z field for scaling properties of its zero-value contours. We find for the first time for three-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…The values of the cancellation exponent found in this study confirm a phenomenological relation for conformal invariant systems between the cancellation exponent and the diffusivity of the Brownian process in the equivalent SLE system derived in Ref. [41].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The values of the cancellation exponent found in this study confirm a phenomenological relation for conformal invariant systems between the cancellation exponent and the diffusivity of the Brownian process in the equivalent SLE system derived in Ref. [41].…”
Section: Discussionsupporting
confidence: 70%
“…For the particular case of rotating helical turbulence, in Ref. [41] it was found that only the vertically averaged vertical velocity and vorticity display conformally invariant behavior, with the same scaling for both the vertical velocity and vertical vorticity, and with κ SLE = 3.6 ± 0.1 measured for the vertical vorticity. It is important to note that the relation given by Eq.…”
Section: Cancellation Exponentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the two-dimensional inverse cascade for fluids has been found to be conformal invariant [32], making the bridge between turbulence and critical phenomena more evident. Conformal invariance has also been detected in three dimensions in the presence of strong rotation [33].…”
mentioning
confidence: 92%
“…As the diffusivity of the Brownian driving function varies, a continuum of universality classes is obtained, and correspondences to numerous models in statistical mechanics have been discovered, including the Ising model [6] (even in three dimensions [7]), spin glasses [8], the Ashkin-Teller model [9], the Potts model [10], walks and polymers on the lattice [1,11,12,13], non-equilibrium phenomena [14,15] (even in three dimensions [16]), and the Gaussian free field [17]. A deep connection to Conformal Field Theory (CFT) has been unveiled [18], as well as with logarithmic CFT [19,20], and some generalizations of SLE have been based on it [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%